Transcending Borders - Carool Kersten (International Institute of Islamic Thought, 2005)
This collection of essays is a spin-off of a workshop held in December 1997, which was jointly organized by the venerable Koninklijk Instituut voor Taal-, Land- en Volkenkunde (the Royal Institute of Linguistics and Anthropology) and the more recently established International Institute of Asian Studies in Leiden, the Netherlands. Both are important resource centers for the study of Islam in Southeast Asia and are closely connected with Leiden University, which has a formidable reputation as a centuries-old center of learning in Islamic and Asian studies. Publications like the present one show that academic institutions with roots in the colonial past and which were once part of the now much-criticized scholarly tradition of “Orientalism” can reinvent themselves and continue to make valuable contributions to the study of non-western cultures. Transcending Borders focuses on the phenomenon of Arab settlement in Southeast Asia. Although the role of these migrants in the Islamization of the Malay–Indonesian archipelago has long been acknowledged, questions pertaining to their integration into Southeast Asian society and the resulting impact on their ethnic identity have received far less attention. In fact, the upsurge in research into these aspects is barely a decade old. However, the most recent developments in Muslim Southeast Asia will certainly keep that interest alive, because some of the more militant key players in Southeast Asian Islamic revivalism are themselves of Hadrami or southern Arabian descent. The book’s 10 articles approach the study of Arab migration and settlement from historical, sociological, anthropological, and Islamological perspectives. However, the editors have taken care to ensure that these different approaches provide intersecting images of the Arab presence in ...